Hedonic Evaluation of Red Ginger Extract Gummy Candy as an Innovative Approach to Prevent Stunting in Children Under Five - Heryani, Heni; Nugraha, Davit; Lestari, Lusi; Rahmah Kurnia, Siti; Yusuf, Anna L (Inspirasi Foundation, 2024)
Introduction: Stunting can have long-term impacts on children's health and development. Preventing stunting in children under five requires a comprehensive approach, including adequate and balanced nutritional intake. One of the natural ingredients commonly used in traditional medicine is red ginger (Zingiber officinale var. rubrum), which contains phytochemical compounds, vitamins, minerals, and fiber beneficial for maintaining vascular and digestive health. Gummy candy formulations have the advantage of high acceptability and appeal, particularly for children who find it difficult to consume medicine. Objective: This study aims to determine the level of preference for gummy candy made with red ginger extract as a strategy to prevent stunting in children under five. Method: The study employed an experimental design using a sensory hedonic test. The inclusion criteria included mothers with toddlers. A total of 20 participants were selected using an incidental sampling technique. Result: The findings indicated that participants showed a high level of preference for red ginger extract gummy candy. On average, the gummy candy was rated as highly appealing in terms of appearance, taste, aroma, and texture. Conclusion: Red ginger extract gummy candy has significant potential to be well-accepted by children under five. Further improvements are recommended, particularly in enhancing the gummy candy's appearance and incorporating more varied shapes to increase its appeal.